1992
DOI: 10.1016/0014-5793(92)80363-l
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral‐mediated transfer of a dystrophin minigene into mdx mouse myoblasts in vitro

Abstract: We have demonstrated expression of a 6.3 kb Becker muscular dystrophy (BMD) haman dystrophin cDNA following retroviral-mediated transduction of cultured myoblasts from the dystrophin-deficient rod.x" mouse. The truncated dystrophin protein was localiscd to the sarcolcmma of differentiated myotube5 by antibodies against the C.terminus el'the molecule, and produced an identical immunostaining pattern to that observed in control myotubes expressing normal endogenous dystrophin. These results indicate that retrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…In fact, the poor level of transduction in mature muscle with various viral vectors (adenovirus, retrovirus and herpes simplex virus) remains a major obstacle to the application of gene therapy for DMD. [36][37][38][39][40][41][42][52][53][54] To compare the relative dystrophin gene transfer efficiency between dystrophin-containing adenoviral particles for direct injection with that obtained when the same adenovirus preparation is used in an ex vivo protocol, 1 × 10 7 AdDYS␤gal viral particles were either injected directly into an mdx leg muscle site, or used to infect 1 × 10 6 primary mdx muscle cells that were subsequently injected into the contralateral mdx leg muscle site. Analysis of the sites 5 days after injection indicated a nearly 10-fold greater number of dystrophin-positive muscle fibers in mdx sites treated with the ex vivo cell transfer protocol compared with that obtained via direct adenovirus injection (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the poor level of transduction in mature muscle with various viral vectors (adenovirus, retrovirus and herpes simplex virus) remains a major obstacle to the application of gene therapy for DMD. [36][37][38][39][40][41][42][52][53][54] To compare the relative dystrophin gene transfer efficiency between dystrophin-containing adenoviral particles for direct injection with that obtained when the same adenovirus preparation is used in an ex vivo protocol, 1 × 10 7 AdDYS␤gal viral particles were either injected directly into an mdx leg muscle site, or used to infect 1 × 10 6 primary mdx muscle cells that were subsequently injected into the contralateral mdx leg muscle site. Analysis of the sites 5 days after injection indicated a nearly 10-fold greater number of dystrophin-positive muscle fibers in mdx sites treated with the ex vivo cell transfer protocol compared with that obtained via direct adenovirus injection (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Retroviral vectors are capable of introducing truncated dystrophin to dystrophic myoblasts in vitro, but are unable to efficiently transduce differentiated muscle cells such as myotubes and myofibers, since they require dividing cells for integration and expression. 36,37 While adenovirus (AV) appears to be a relatively good vector for skeletal muscle cells, there are potential limitations to the use of AV as a gene delivery vector to muscle, ie the differential transducibility of myofibers throughout muscle maturation; the immune rejection induced by first generation adenoviral vectors; and the high titer of viral recombinants that is often required for successful muscle transduction. [38][39][40][41][42][43][44][45][46][47] Recent studies with mutant AV vectors in which all viral genes were removed, suggest that these vectors may be able to circumvent the immunological problems due to viral antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that a truncated (6.3 kb) human dystrophin cDNA can be retrovirally transduced and expressed in mdx mouse myoblasts in vitro (Dunckley et al, 1992), and that retroviral transduction of activated satellite cells in regenerating skeletal muscle can facilitate direct and stable dystrophin gene transfer into muscle tissues in vivo (Dunckley et al, 1993). Because the retrovirus requires dividing cells for its integration, the ongoing process of muscle degeneration and regeneration that occurs in mdx mouse skeletal muscle is thought to promote the efficient retroviral transduction observed in skeletal muscle in vivo.…”
Section: Introduction D Uchenne's Muscular Dystrophy (Dmd) Is Charactmentioning
confidence: 99%
“…Effective gene therapy for DMD will require the transfer of adequate copies of either the full-length dystrophin gene or dystrophin minigenes in affected muscle to restore adequate production of dystrophin for compensation of the weakness. [6][7][8][9][10] The transplantation of normal myoblasts into dystrophin-deficient muscle to create a reservoir of dystrophinproducing myoblasts capable of fusing with dystrophic myofibers has been studied extensively in both mdx mice (an animal model for DMD) and DMD patients. [11][12][13][14][15][16] Although these studies showed transient restoration of dystrophin and increase of strength in dystrophic muscle, the limited success of myoblast transplantation has been related to immune rejection, poor survival and limited spread of injected myoblasts after transplantation.…”
Section: Introductionmentioning
confidence: 99%